HLA-mismatched stem cell microtransplant prolonged overall survival and promoted immunological reconstitution for multiple myeloma - Lei, Yangyang; Cai, Bo; Liu, Zhiqing; Xie, Anli; Qiao, Jianhui; Wang, Yi; Chen, Xinrui; Peng, Fei; Zhao, Yingxin; Chen, Jiaxin; Guan, Wei; Yu, Changlin; et al. (Frontiers in Immunology, 2025)
BackgroundDespite advances in the treatment of multiple myeloma, a proportion of patients still hardly achieve desired prognosis. Although microtransplant (MST) has proved promising results in treating several hematological malignancies, it has not been studied in multiple myeloma.MethodsWe performed a retrospective analysis of multiple myeloma patients treated with MST at our institution. Their clinical information and outcome measurements were collected. Furthermore, the fluctuation of donor microchimerism after MST, as well as the alteration of immune function before and after MST were analyzed.ResultsTwenty patients receiving MST were enrolled from June 2008, to May 2024, with an overall response rate of 17/20. The 6-year overall survival (OS) and progression-free survival (PFS) rates were 64.7% and 35.3%, respectively, with no graft-versus-host disease or non-relapse mortality. Incidence of controlled fever and Grade I cytokine release syndrome (CRS) was 40.8%. The OS were comparable between groups with age, International Staging System stage, and Mayo Stratification of Myeloma and Risk-Adapted Therapy stage. However, earlier Durie-Salmon stage, disease in VGPR or CR status prior to MST, and an increase in total cycle number of MST were significantly associated with longer OS. Donor microchimerism was detected in all available peripheral blood samples from 14 days to 6 months post-MST. Furthermore, MST resulted in increased proportions of total CD3+ T cells, and CD4+CD8- T cells in peripheral blood, as well as improved CD4:CD8 ratio and increased proportions of Th0 cells.ConclusionMST extended PFS and OS, and benefit immune reconstitution in multiple myeloma patients. Therefore, MST is a promising treatment for multiple myeloma, especially those with high-risk cytogenetics.